Pengaruh Model Kooperatif Tipe STAD Berbantuan Media Audiovisual terhadap Hasil Belajar Tematik Kelas V Sekolah Dasar - Evianti, Tania Henita; T, Ahmad Yani; Halidjah, Siti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The purpose of this study was to analayzed the effect of the STAD-type cooperative learning model assisted by audio-visual media on the thematic learning outcomes of fifth grade at SDN 35 Pontianak Selatan. The quasi-experimental form was used in this study. The population was 102 students. Simple random sampling method was used to determine the research sample. Items in the form of short answers are used as research instruments. The results of the pre-test and post-test were analyzed using measurement techniques.The average cognitive learning outcomes of the control class were 67.28 and that of the experimental class was 76.03. After conducting the t test, it is obtained tcount (2.417) with ttable (α = 5% and dk = 59) of 2.0011, because tcount (2.417) > ttable (2.0011) then Ha is accepted. The average learning outcomes in the psychomotor domain of the control class was 74.31 and the experimental class was 79.41, obtained tcount (4.180) while ttable (α = 5% and dk = 65) was 1.999 so it can be seen that tcount (4.180) > ttable (1.999) ), thus Ha is accepted. Calculation of the cognitive domain effect size of 0.63 (moderate category). The effect size calculation for the psychomotor domain is 1.024 (high category). Therefore, the STAD cooperative learning approach with the use of audio-visual media has an impact on the thematic learning outcomes of fifth grade students at SDN 35 Pontianak Selatan.